2007
DOI: 10.1016/j.immuni.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine Kinase-Sphingosine-1-Phosphate Axis Is a Determinant of Mast Cell Function and Anaphylaxis

Abstract: Sphingosine-1-phosphate, a key mediator in immune cell trafficking, is elevated in the lungs of asthmatic patients and regulates pulmonary epithelium permeability. Stimulation of mast cells by allergens induces two mammalian sphingosine kinases (Sphk1 and Sphk2) to produce sphingosine-1-phosphate (S1P). Little is known about the individual role of these kinases in regulating immune cell function. Here we show that in mast cells, Sphk2 is required for production of S1P, for calcium influx, for activation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
250
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(272 citation statements)
references
References 57 publications
20
250
2
Order By: Relevance
“…This observation is reminiscent of the dependency on SphK2 expression for TNF-␣ secretion by fetal mouse liver-derived mast cells. 10 These results indicate that SphK2 might play an important role in regulation of release of this cytokine that is important for exacerbation of allergic responses and is overproduced in asthmatic subjects. 30 Altogether, our study reinforces the notion that SphK1 and S1P are critical for hMC activation and functions that have been implicated in allergic responses, such as asthma and anaphylaxis.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…This observation is reminiscent of the dependency on SphK2 expression for TNF-␣ secretion by fetal mouse liver-derived mast cells. 10 These results indicate that SphK2 might play an important role in regulation of release of this cytokine that is important for exacerbation of allergic responses and is overproduced in asthmatic subjects. 30 Altogether, our study reinforces the notion that SphK1 and S1P are critical for hMC activation and functions that have been implicated in allergic responses, such as asthma and anaphylaxis.…”
mentioning
confidence: 84%
“…9 Based on results with fetal liver-derived MCs from SphK1 Ϫ/Ϫ , SphK2 Ϫ/Ϫ , and SphK1 Ϫ/Ϫ SphK2 Ϫ/Ϫ mice, it was suggested that SphK2, but not SphK1, may modulate calcium influx and downstream signaling, particularly PKC␣ and ␤, leading to degranulation and the production of eicosanoids and cytokines. 10 By contrast, passive systemic anaphylaxis was impaired in SphK1 Ϫ/Ϫ mice, but not in SphK2 Ϫ/Ϫ mice, and plasma histamine levels were correlated with SphK1 expression and circulating levels of S1P. Hence, it was suggested that SphK2 is a determinant of intrinsic MC function, whereas SphK1 plays an extrinsic role.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, circulating S1P (generated mostly by SphK1) and intrinsic mast cell SPHK2 together determine the anaphylactic response, a phenomenon that involves degranulation, which is a specialized form of exocytosis. SphK2-null mice show defective PKC translocation, NF-κB activation, and calcium influx, which are all part of the regular anaphylactic response [190]. SphK1 -/-SphK2 -/-double mutants die as embryos, although the embryos appear normal until E9.5.…”
Section: Sphingosine Kinases and S1pmentioning
confidence: 99%